1997
DOI: 10.1023/a:1018477232354
|View full text |Cite
|
Sign up to set email alerts
|

Untitled

Abstract: Hoplias malabaricus, a widely distributed neotropical fish (Central America to Argentina), may represent a group of distinct species showing diversified cytotypes with respect to chromosome number, morphology and sex systems. One of these karyotypic forms is characterized by an X1X1X2X2/X1X2Y sex chromosome system, with 2n = 40 and 39 chromosomes in females and males respectively. Analyses with G-, C- and chromosome replication banding permitted a better characterization of the sex chromosomes in this cytotype… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

2
11
0

Year Published

2000
2000
2017
2017

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 88 publications
(13 citation statements)
references
References 11 publications
2
11
0
Order By: Relevance
“…The distribution of heterochromatin in all the karyomorphs of the Hoplias malabaricus complex has often been described in the terminal and pericentromeric region of some pairs of chromosomes ( Dergam and Bertollo 1990 , Haff et al 1993 , Bertollo et al 1997a , 1997b , Born and Bertollo 2000 , Vicari et al 2005 , Blanco et al 2010 ), and was also observed in the population of the present study. However, a small variation in the amount and location of heterochromatin can be observed between the various allopatric populations already studied (i.e., Blanco et al 2010 ).…”
Section: Discussionsupporting
confidence: 83%
“…The distribution of heterochromatin in all the karyomorphs of the Hoplias malabaricus complex has often been described in the terminal and pericentromeric region of some pairs of chromosomes ( Dergam and Bertollo 1990 , Haff et al 1993 , Bertollo et al 1997a , 1997b , Born and Bertollo 2000 , Vicari et al 2005 , Blanco et al 2010 ), and was also observed in the population of the present study. However, a small variation in the amount and location of heterochromatin can be observed between the various allopatric populations already studied (i.e., Blanco et al 2010 ).…”
Section: Discussionsupporting
confidence: 83%
“…Three well-differentiated sex chromosome systems occur in this group, namely XX/XY in karyomorph B, X 1 X 1 X 2 X 2 /X 1 X 2 Y in karyomorph D and XX/XY 1 Y 2 in karyomorph G; additionally, karyomorph C has an early differentiated XX/XY system [18,19]. Karyomorph D has 2n = 40 chromosomes in females and 2n = 39 chromosomes in males; repetitive DNA chromosomal mapping suggests that karyomorph D may have derived from a karyotype similar to karyomorph C, which is characterized by 2n = 40 chromosomes in both sexes [19,20]. A conspicuous proximal GC-rich heterochromatic/18S rDNA site, which is present on the long arms of the X and Y chromosomes in karyomorph C, is also located in the same region on the X 1 chromosome and the short arm of the large Y chromosome of karyomorph D; this suggests that the X 1 and Y chromosomes of karyomorph D derived from the XY chromosomes of karyomorph C. In addition, the Y chromosome of karyomorph D shares similar DNA sequences with chromosomes Y and 20 of karyomorph C. Chromosomal pair number 20 in karyomorph C and its homolog in karyomorph D (X 2 ) have centromeric satellite 5S Hind III-DNA, as well as an exclusive interstitial site that is present on the long arms of the Y chromosome of karyomorph D, which is the only non-centromeric location of this DNA sequence in the entire karyotype.…”
Section: Introductionmentioning
confidence: 99%
“…These data indicate that this interstitial site is derived from the centromere of chromosome 20, which was fused to the ancestral Y chromosome in karyomorph C and resulted in the dicentric Y chromosome currently present in karyomorph D [19]. Moreover, additional studies have shown that this dicentric Y chromosome behaves as a stable component of the karyotype having a correct segregation during meiosis [20]. …”
Section: Introductionmentioning
confidence: 99%
“…The systems with male heterogamety have the first records in Neotropical fish in the genera Hoplias, with multiple sex chromosomes such as X 1 X 1 X 2 X 2 /X 1 X 2 Y and XX/XY 1 Y 2 [ 65 ], and Eigenmannia, with a X 1 X 1 X 2 X 2 /X 1 X 2 Y system [ 66 ].…”
Section: The Origin and Differentiation Of Sexual And B Chromosomementioning
confidence: 99%